The case of the speluncean explorers : nine new opinions - Suber, Peter (London ; New York : Routledge, 1998)
Lon L. Fuller published his "The Case of the Speluncean Explorers" in 1949 (Harvard Law Review, vol. 62, no. 4), an invented legal case with opinions by "supreme court judges" meant to reflect differing legal philosophies. It is reprinted here, with nine new opinions by Peter Suber.
pt. 1. Lon Fuller's Case of the speluncean explorers -- pt. 2. Nine new options.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Fuller, Lon L. -- 1902-1978 -- Contributions in law; Fuller, Lon L. -- Contributions in law; Fuller, Lon L. -- 1902-1978; Fuller, Lon L; Law -- Philosophy; LAW -- Jurisprudence; LAW -- General Practice; LAW -- Reference; LAW -- Essays; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; Law -- Philosophy; Law; Law -- Philosophy; Rechtsphilosophie; Law; Law